Prevalence of Blood Parasites Infestation among Buffaloes with Abortion in Nakhon Phanom Province, Thailand - Srisai, Prakit; Pholpark, Manvika; Tongpan, Pichet; Jiwaganon, Netchanok; Punnurit, Parinya; Dermpun, Supranee; Rungruang, Haruthai; Panlinfa, Noppadol (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2017)
From 2007 to 2011, the buffalo population in Nakhon Phanom Province decreased 34% with approximately 150-300 aborted buffaloes each year. However, the etiology was not systematically examined. Our objectives were to determine prevalence of blood parasites in buffaloes with abortion, and identify causes and possible factors related to abortion. We conducted a case control study in Nakhon Phanom from April 2011 to March 2012. Cases were buffaloes that reported abortion and controls were female buffaloes that previously calved without history of abortion in the same sub-district with the case. Farmers were interviewed, and placenta, aborted fetus, blood, serum, and fecal specimens were collected from both cases and controls. The specimens were tested for blood parasites, brucellosis, and gastrointestinal parasites and hematocrit using Giemsa staining of blood smear and hematocrit centrifugation technique by Woo’s method, and identified for blood parasites by microscopy. Trypanosoma spp. was the only blood parasite found with the true prevalence of 16% (95% CI =2.6-30.0). We identified risk factors for abortion using logistic regression. Significant risk factors for abortion were high density of tabanus (adjusted OR=12.9, 95% CI=1.2-135.7) and blood parasite (adjusted OR=13.1, 95% CI=1.2-142.9). Reducing the density of the vector such as tabanus might reduce the risk of abortion in buffaloes. In addition, a surveillance system on abortion etiology should be established.